2018
DOI: 10.1016/j.jid.2018.03.1525
|View full text |Cite
|
Sign up to set email alerts
|

CARD14 Gain-of-Function Mutation Alone Is Sufficient to Drive IL-23/IL-17–Mediated Psoriasiform Skin Inflammation In Vivo

Abstract: Rare autosomal dominant mutations in the gene encoding the keratinocyte signaling molecule CARD14, have been associated with an increased susceptibility to psoriasis, but the physiological impact of CARD14 gain-of-function mutations remains to be fully determined in vivo. Here, we report that heterozygous mice harboring a CARD14 gain-of-function mutation (Card14ΔE138) spontaneously develop a chronic psoriatic phenotype with characteristic scaling skin lesions, epidermal thickening, keratinocyte hyperproliferat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
83
0
3

Year Published

2018
2018
2021
2021

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 82 publications
(90 citation statements)
references
References 65 publications
4
83
0
3
Order By: Relevance
“…This suggests a similar mechanism of activation, via induction of an active CARD14 conformation and oligomerization necessary for CBM complex formation and downstream signaling events. In support of this model, a recent study showed that a single point mutation in CARD14 E138A, which renders CARD14 hyperactive, was sufficient to drive spontaneous psoriasis disease in mice (125). Inhibition of MALT1 protease activity effectively reduces cytokine and chemokine expression induced by overexpression of this hyperactive CARD14 mutant in human primary keratinocytes (126).…”
Section: Malt1 Deregulation Is Associated With Allergy Inflammatory mentioning
confidence: 93%
“…This suggests a similar mechanism of activation, via induction of an active CARD14 conformation and oligomerization necessary for CBM complex formation and downstream signaling events. In support of this model, a recent study showed that a single point mutation in CARD14 E138A, which renders CARD14 hyperactive, was sufficient to drive spontaneous psoriasis disease in mice (125). Inhibition of MALT1 protease activity effectively reduces cytokine and chemokine expression induced by overexpression of this hyperactive CARD14 mutant in human primary keratinocytes (126).…”
Section: Malt1 Deregulation Is Associated With Allergy Inflammatory mentioning
confidence: 93%
“…A very recent study found that IL-17 and IL-22 promote keratinocyte stemness (Ekman et al, 2019). In two studies, it was shown that mice with a gain-of-function mutation of the card14 gene, a known risk locus for human psoriasis, developed spontaneous psoriasis-like skin inflammation triggered by IL-17 mostly derived from αβ T cells acting on keratinocytes (Mellett et al, 2018;Wang et al, 2018). This was mediated by intracellular CARMA2 accumulation and activation.…”
Section: Il-17 Immunitymentioning
confidence: 99%
“…CARD14 encodes a member of the membrane‐associated guanylate kinase family, and falls within PSORS2 , the psoriasis susceptibility 2 locus . CARD14 is known to activate NF‐κB, while increasing the expression of inflammatory factors including tumor necrosis factor alpha (TNFα), interleukin‐17 (IL‐17), chemokine ligand 8 (CXCL‐8), and interleukin‐36γ (IL‐36γ) . These are canonical pathways implicated in psoriasis.…”
Section: Introductionmentioning
confidence: 99%